Method for producing zinc phenylphosphonate, powder of zinc phenylphosphonate, use thereof as crystal nucleating agent and moisture-curable hot-melt polyurethane resin adhesive

The zinc phenylphosphonic acid powder was prepared by reacting phenylphosphonic acid with zinc compound in the presence of polyethylene glycol in water, and used as a crystal nucleation agent, which solved the problem of insufficient curing time of polyurethane resin and improved the curing speed and initial strength.

CN119278204APending Publication Date: 2025-01-07DIC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280096770.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-09-15
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

On wooden packaging and high-speed production lines of decorative panels requiring initial strength, polyurethane resins often fail to cool and cure, resulting in problems in the next process. The prior art uses phenylphosphonic acid metal salt as crystallization nucleating agent to cure when using phenylphosphonate metal salt as crystallization nucleating agent. There is still room for improvement in time.

Method used

React phenylphosphonic acid with zinc compound in water, and add polyethylene glycol as coexisting substances to prepare zinc phenylphosphonate and its powder as crystallization nucleation agent to shorten the curing time of wet curable hot melt polyurethane resin .

Benefits of technology

Through this method, the curing time of the polyurethane resin is significantly shortened, the initial creep performance and initial peel strength are improved, and the performance of the adhesive is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119278204A_ABST
    Figure CN119278204A_ABST
Patent Text Reader

Abstract

A method for producing zinc salt of phenylphosphonic acid, method comprising step of reacting phenylphosphonic acid represented by formula (1) and zinc compound with each other in water in presence of polyethylene glycol: # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for producing zinc phenylphosphonate, powder of zinc phenylphosphonate, use thereof as a crystal nucleating agent, and a moisture-curable hot-melt polyurethane resin adhesive. Background Art

[0002] Moisture-curable hot-melt polyurethane resins have excellent adhesiveness and can adjust the bonding time relatively freely, so they are suitable for adhesives used in bonding processes that require continuous production and molding processes such as sealing work, and are used in a wide range of fields. However, in applications such as wood packaging for decorative boards that require initial strength, and in applications such as electrical / electronic parts and automotive parts that require continuous production on high-speed production lines, there may be a problem that the parts enter the next process without sufficient cooling and curing of the polyurethane resin.

[0003] In order to solve the above problems, metal salts of phenylphosphonic acid compounds have been added to polyurethane resins as crystal nucleating agents to shorten the curing time. For example, WO2011 / 030822 discloses a method for producing a phenylphosphonic acid metal salt, which is a method for producing a phenylphosphonic acid metal salt suitable as a crystal nucleating agent, wherein a phenylphosphonic acid compound is reacted with a metal salt, a metal oxide or a metal hydroxide in an amount exceeding an equivalent amount of the phenylphosphonic acid compound. SUMMARY OF THE INVENTION

[0005] According to the research of the inventors of the present invention, when a phenylphosphonic acid metal salt is used as a crystal nucleating agent, there is still room for further shortening the curing time of the moisture-curable hot-melt polyurethane resin.

[0006] In view of these circumstances, an object of one aspect of the present invention is to provide a method for producing a zinc salt of phenylphosphonic acid, which can be suitably used as a crystallization nucleating agent that can further shorten the curing time of a moisture-curable hot-melt polyurethane resin, and a powder of the zinc salt of phenylphosphonic acid. Another object of the present invention is to provide a moisture-curable hot-melt polyurethane resin adhesive having a further shortened curing time.

[0007] The inventors of the present invention have found that when phenylphosphonic acid and a zinc compound react with each other in water, by making polyethylene glycol coexist, a phenylphosphonic acid zinc salt and a powder thereof which can be suitably used as a crystal nucleating agent that can further shorten the curing time of a moisture-curable hot-melt polyurethane resin can be obtained.

[0008] The present invention includes the following aspects.

[0009] [1] A method for producing a phenylphosphonic acid zinc salt, the method comprising the step of reacting phenylphosphonic acid represented by formula (1) and a zinc compound with each other in water in the presence of polyethylene glycol:

[0010] .

[0011] [2] The method for producing a phenylphosphonic acid zinc salt according to [1], wherein the amount of the zinc compound is 1 mol or less relative to 1 mol of the phenylphosphonic acid represented by the formula (1).

[0012] [3] A powder of phenylphosphonic acid zinc salt represented by formula (2), the phenylphosphonic acid zinc salt being obtained by the method for producing phenylphosphonic acid zinc salt according to [1] or [2]:

[0013] .

[0014] [4] Use of the powder according to [3] as a crystal nucleating agent.

[0015] [5] A moisture-curable hot-melt polyurethane resin adhesive comprising an isocyanate-terminated polyurethane prepolymer and the powder according to [3].

[0016] [6] The moisture-curable hot-melt urethane resin adhesive according to [5], wherein the content of the powder is 0.1 to 10% by mass based on the entire amount of the moisture-curable hot-melt urethane resin adhesive.

[0017] One aspect of the present invention can provide a method for producing a zinc phenylphosphonate salt and a powder of the zinc phenylphosphonate salt, which can be suitably used as a crystallization nucleating agent that can further shorten the curing time of a moisture-curable hot-melt polyurethane resin. Another aspect of the present invention can provide a moisture-curable hot-melt polyurethane resin adhesive having a further shortened curing time.

[0018] Description of the implementation plan

[0019] The embodiments of the present invention are described in detail below. One embodiment of the present invention is a method for producing a phenylphosphonic acid zinc salt, the method comprising the step of reacting a phenylphosphonic acid represented by formula (1) and a zinc compound with each other in the presence of polyethylene glycol in water (reaction step):

[0020] .

[0021] In the reaction step, for example, the phenylphosphonic acid represented by the formula (1) and the zinc compound are reacted by adding an aqueous solution of the zinc compound dissolved in water and a solution of polyethylene glycol dissolved in a solvent to an aqueous solution of the phenylphosphonic acid represented by the formula (1) dissolved in water. During this process, for example, the above reaction can be carried out by gradually adding an alkaline aqueous solution (e.g., an aqueous sodium hydroxide solution).

[0022] The amount of water in the aqueous solution of phenylphosphonic acid represented by formula (1) may be 1,000 parts by mass or more, 2,000 parts by mass or more, or 3,000 parts by mass or more, and 10,000 parts by mass or less, 7,000 parts by mass or less, or 5,000 parts by mass or less, relative to 100 parts by mass of the phenylphosphonic acid represented by formula (1).

[0023] The zinc compound may be, for example, zinc halide, zinc oxide or zinc acetate. The zinc halide may be zinc fluoride, zinc chloride, zinc bromide or zinc iodide.

[0024] The amount of water in the aqueous solution of the zinc compound may be 500 parts by mass or more, 1,000 parts by mass or more, or 2,000 parts by mass or more, and 5,000 parts by mass or less, 4,000 parts by mass or less, or 3,000 parts by mass or less, relative to 100 parts by mass of the zinc compound.

[0025] The amount of the zinc compound may be 0.8 mol or more, 0.9 mol or more, or 0.95 mol or more, and 1.1 mol or less, 1.05 mol or less, or 1 mol or less, relative to 1 mol of the phenylphosphonic acid represented by formula (1).

[0026] The number average molecular weight (Mn) of the polyethylene glycol may be 200 or more, 500 or more, or 800 or more, and 2,000 or less, 1,500 or less, or 1,200 or less.

[0027] The solvent for dissolving polyethylene glycol may be an alcohol. The alcohol may be an aliphatic alcohol. Examples of alcohols include methanol, ethanol, 1-propanol, 2-propanol, and ethylene glycol.

[0028] The amount of the solvent in the polyethylene glycol solution may be 100 parts by mass or more, 150 parts by mass or more, or 200 parts by mass or more, and 400 parts by mass or less, 350 parts by mass or less, or 300 parts by mass or less, relative to 100 parts by mass of polyethylene glycol.

[0029] The white precipitate precipitated by the reaction step is filtered out, washed with water, and then dried to obtain the phenylphosphonic acid zinc salt represented by formula (2) as a powder (white powder). That is, another embodiment of the present invention is a powder of the phenylphosphonic acid zinc salt represented by formula (2) obtained by the production method:

[0030] .

[0031] The powder of zinc phenylphosphonate represented by formula (2) is obtained by the production method, and can thereby further shorten the curing time of moisture-curable hot-melt polyurethane resin compared with, for example, commercially available powder of zinc phenylphosphonate. Although it is not clear what structure or characteristics of the powder of zinc phenylphosphonate represented by formula (2) contribute to this effect, the inventors of the present invention presume that the reason for the above effect is as follows.

[0032] Polyethylene glycol can function as a dispersion medium in the reaction step, whereby when crystals of zinc phenylphosphonate represented by formula (2) are formed, the dispersibility of the crystals in water becomes favorable, and crystals (powder) with less flocculation can be obtained. Therefore, it is believed that when the powder is mixed with a polyurethane resin as a crystal nucleating agent, the contact area between the crystal nucleating agent and the polyurethane resin is large, thereby promoting the crystallization of the polyurethane resin.

[0033] In one embodiment, the phenylphosphonic acid zinc salt powder represented by formula (2) is obtained by the production method, and thus it is also possible to achieve, for example, a reduction in the tack-free time of the moisture-curable hot-melt polyurethane resin adhesive, an improvement in the initial creep properties, and an increase in the initial peel strength, compared with commercially available phenylphosphonic acid zinc salt powder.

[0034] As described above, the powder of zinc phenylphosphonate represented by formula (2) can be suitably used as a crystal nucleating agent, more specifically, as a crystal nucleating agent for promoting crystallization of polyurethane resin. That is, another embodiment of the present invention is the use (application) of the powder of zinc phenylphosphonate represented by formula (2).

[0035] Another embodiment of the present invention is a moisture-curable hot-melt polyurethane resin adhesive comprising an isocyanate group-terminated polyurethane prepolymer and a powder of a phenylphosphonic acid zinc salt represented by the above formula (2).

[0036] The isocyanate group-terminated polyurethane prepolymer can be obtained by reacting a polyol (A) and a polyisocyanate (B) with each other in the presence of a phenylphosphonic acid zinc salt represented by the above formula (2) and a zinc phosphate complex represented by the above formula (4).

[0037] The polyol (A) may contain an aliphatic polyester polyol, two aliphatic polyester polyols (the aliphatic polyester polyol (a1) and the aromatic polyester polyol (a2) described below), or two aliphatic polyester polyols (the aliphatic polyester polyol (a1) and the aromatic polyester polyol (a2) described below) and another polyol (a3) ​​other than the aliphatic polyester polyol.

[0038] The aliphatic polyester polyol (a1) is a polyester polyol produced by a known conventional method using an aliphatic polycarboxylic acid and an aliphatic polyol as main components, and the production method thereof is not limited to a specific method.

[0039] Preferred examples of the aliphatic polycarboxylic acid used for synthesizing the aliphatic polyester polyol (a1) include 4-12 Aliphatic polycarboxylic acids such as succinic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decanedioic acid, dodecanedioic acid, eicosanedioic acid, citric acid, itaconic acid, citraconic anhydride and itaconic anhydride.

[0040] For example, as for the aliphatic polycarboxylic acid, lower alkyl ester derivatives such as methyl ester, acid anhydride and corresponding acid derivatives such as acid halide can be used.

[0041] The aliphatic polyol used for synthesizing the aliphatic polyester polyol (a1) is an aliphatic polyol having at least two hydroxyl groups in the molecule, preferably C 2-12 The aliphatic polyol (a1) may be linear, branched or cyclic in structure.

[0042] Examples of the aliphatic polyols include straight-chain aliphatic polyols such as ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, diethylene glycol, triethylene glycol, triethylene glycol and tetraethylene glycol; branched-chain aliphatic polyols such as neopentyl glycol, 1,3-butanediol, 2,2-diethyl-1,3-propanediol, 2,2-diethylpropylene glycol, 3-methyl-1,5-pentanediol, 2-ethyl-2-butyl-1,3-propanediol, 2-methyl-1,8-octanediol, 2,4-diethyl-1, 5-pentanediol, trimethylolethane, trimethylolpropane and pentaerythritol; and alicyclic polyols such as cyclopentanediol, cyclohexanediol, cyclohexanedimethanol. Among them, ethylene glycol, 1,6-hexanediol and neopentyl glycol are preferred.

[0043] Adducts of various alkylene oxides added to hydrogenated bisphenol A, hydrogenated bisphenol F, etc. can also be used. Polymerization products obtained by ring-opening polymerization of γ-butyrolactone, ε-caprolactone, etc. using low molecular weight polyols as initiators can also be used. These can be used alone or in combination of two or more.

[0044] In the combination of aliphatic polycarboxylic acid and aliphatic polyol, the polyol (A) contains C 4-12 Aliphatic polycarboxylic acid and C 2-12The aliphatic polyester polyol (a1) produced by the combination of aliphatic polyols further improves the viscosity stability of the hot melt polyurethane resin adhesive during the molding process and can produce an excellent effect of preventing the melt viscosity from decreasing, which is preferred.

[0045] The aromatic polyester polyol (a2) is a polyester polyol produced by a known conventional method using aromatic polycarboxylic acid and aliphatic polyol or aliphatic polycarboxylic acid and aromatic polyol as main components, and the production method is not limited to a specific method.

[0046] Aromatic polycarboxylic acids are carboxylic acids in which at least two carboxyl groups are bonded to aromatic rings, and are preferably C 8-24 Aromatic polycarboxylic acids. Examples thereof include phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, pyromellitic acid, biphenyl dicarboxylic acid, and naphthalene dicarboxylic acid. These may be used alone or in combination of two or more.

[0047] For example, for the aromatic polycarboxylic acid, lower alkyl ester derivatives such as methyl ester, acid anhydride and corresponding acid derivatives such as acid halide can be used.

[0048] Examples of the aliphatic polyol include the same aliphatic polyols as those which can be used for synthesizing the aliphatic polyester polyol (a1).

[0049] The aliphatic polyols that can be used to synthesize the aromatic polyester polyol (a2) and the aliphatic polyester polyol (a1) can be diethylene glycol, triethylene glycol, tetraethylene glycol, 1,4-bis(β-hydroxyethoxy)benzene, etc., wherein part of the carbon atoms thereof are substituted by oxygen atoms or aromatic rings. These aliphatic polyols can also be used alone or in combination of two or more.

[0050] Furthermore, it is also possible to use mixtures of polyester polyols derived from aromatic polycarboxylic acids and aliphatic polyols.

[0051] Examples of aliphatic polycarboxylic acids that can be used to synthesize the aromatic polyester polyol (a2) include C 4-12 Aliphatic polycarboxylic acid, which is the same as that exemplified as the aliphatic polycarboxylic acid which can be used for synthesizing the aliphatic polyester polyol (a1).

[0052] The aromatic polyol is not limited to a specific aromatic polyol. Examples thereof include aromatic polyols obtained from aliphatic polyols such as ethylene glycol and neopentyl glycol and aromatic polycarboxylic acids such as phthalic acid and terephthalic acid.

[0053] As the aromatic polyol, for example, adducts obtained by adding alkylene oxides such as ethylene oxide, propylene oxide and butylene oxide to bisphenol A, bisphenol F or the like can also be used.

[0054] In the synthesis process of the aliphatic polyester polyol (a1) and the aromatic polyester polyol (a2), the equivalent ratio of the hydroxyl groups possessed by the aliphatic polyol and the aromatic polyol to the carboxyl groups of the aliphatic polycarboxylic acid and the aromatic polycarboxylic acid (i.e., [OH / COOH equivalent ratio]) is preferably in the range of 1.03 to 1.50, more preferably in the range of 1.05 to 1.30. When the [OH / COOH equivalent ratio] is in such a range, a larger amount of hydroxyl-terminated polyol can be produced, and the urethanization reaction with the polyisocyanate (B) can be more easily performed, which is preferred.

[0055] The polycondensation conditions in the synthesis process of the aliphatic polyester polyol (a1) and the aromatic polyester polyol (a2) are not limited to specific conditions as long as no abnormal reaction occurs and a normal product can be obtained. Generally, a certain amount of aliphatic polycarboxylic acid and aliphatic polyol or aromatic polycarboxylic acid and aliphatic polyol can be subjected to esterification reaction or transesterification reaction for 5 to 50 hours at an internal temperature of 150 to 250° C. in the presence or absence of a catalyst, and then subjected to polycondensation reaction.

[0056] The polycondensation reaction is preferably carried out in the presence of a catalyst because the reaction proceeds easily. The catalyst is not limited to a specific catalyst. Examples thereof include titanium-based catalysts such as tetrabutoxytitanium and tin-based catalysts such as dibutyltin oxide.

[0057] The catalyst may be added together with the aliphatic polyol and the aliphatic polycarboxylic acid or the aliphatic polyol and the aromatic polycarboxylic acid, or after prepolymerization in the absence of a catalyst.

[0058] In the production of aliphatic polyester polyol (a1) and aromatic polyester polyol (a2), it is desirable to make almost all the ends hydroxyl groups, leaving as few carboxyl groups as possible, and for this purpose, adding the catalyst after conducting prepolymerization is effective and preferred.

[0059] The number average molecular weight (hereinafter referred to as "Mn") of the aliphatic polyester polyol (a1) and the aromatic polyester polyol (a2) is preferably in the range of 500 to 6,000, more preferably in the range of 1,000 to 5,000, particularly preferably in the range of 2,000 to 4,000. When the Mn of (a1) and (a2) is in such a range, a balance of properties such as strength and elongation according to the application can be obtained, which is preferred.

[0060] Examples of other polyols (a3) ​​include polycarbonate polyols, polylactone polyols and polyether polyols. Examples of polycarbonate polyols include polycarbonate polyols obtained using straight-chain aliphatic polyols such as 1,4-butanediol, 1,5-pentanediol and 1,6-hexanediol. Examples of polylactone polyols include polycaprolactone polyols obtained by ring-opening polymerization of caprolactone monomers. Examples of polyether polyols include polyethylene glycol, polypropylene glycol and polybutylene glycol.

[0061] In 100 parts by mass of the polyol (A), the content ratio of aliphatic polyester polyol (a1) / aromatic polyester polyol (a2) / other polyol (a3) ​​may be 20 to 60 parts by mass / 10 to 50 parts by mass / 0 to 50 parts by mass, preferably 30 to 50 parts by mass / 20 to 40 parts by mass / 10 to 20 parts by mass. When the content ratio is within such a range, the melt viscosity of the polyol (A) can be adjusted to an appropriate range, and a moisture-curable hot-melt polyurethane resin adhesive exhibiting excellent processability and miscibility and further excellent curing properties can be obtained.

[0062] Examples of the polyisocyanate (B) include well-known and commonly used aliphatic, aromatic and alicyclic polyisocyanates. Examples thereof include: aromatic diisocyanates such as diphenylmethane diisocyanate (MDI; 4,4' type, 2,4' type, 2,2' type, mixtures thereof, and crude MDI), carbodiimide-modified MDI (modified MDI), polymethylene polyphenyl polyisocyanate, carbodiimidized diphenylmethane polyisocyanate, xylene diisocyanate, toluene diisocyanate (TDI; 2,4 type, 2,6 type and mixtures thereof), xylene diisocyanate (XDI), 1,5 - naphthalene diisocyanate (NDI), tetramethylxylene diisocyanate and phenylene diisocyanate; aliphatic diisocyanates such as hexamethylene diisocyanate (HDI), dimer acid diisocyanate, norbornene diisocyanate, lysine diisocyanate and tetramethylxylene diisocyanate; and alicyclic diisocyanates such as isophorone diisocyanate (IPDI), hydrogenated diphenylmethane diisocyanate (hydrogenated MDI), hydrogenated xylene diisocyanate (hydrogenated XDI), cyclohexane diisocyanate, dicyclohexylmethane diisocyanate and isophorone diisocyanate. Among them, MDI and XDI are preferred because they react quickly with polyol (A) and moisture (water) and have excellent processability. They can be used alone or in combination of two or more.

[0063] The ratio between the polyol (A) and the polyisocyanate (B) used in synthesizing the isocyanate-terminated polyurethane prepolymer (hereinafter referred to as "prepolymer") can be within a range that does not adversely affect the reaction behavior, product quality, etc. In general, the equivalent ratio of the isocyanate group possessed by the polyisocyanate (B) to the hydroxyl group possessed by the polyol (A) (hereinafter referred to as [NCO / OH equivalent ratio]) is preferably within a range of 1.2 to 4.0, and more preferably within a range of 1.5 to 3.0. When the [NCO / OH equivalent ratio] is within such a range, the melt viscosity of the target moisture-curable hot-melt polyurethane resin composition is within an appropriate range, and properties such as excellent processability, film properties, and further excellent curing properties can be exhibited.

[0064] The reaction conditions are not limited to specific conditions as long as they are set within a range that does not adversely affect the reaction behavior, product quality, etc. Generally, the reaction is preferably carried out at a reaction temperature of 80 to 130° C. for 1 to 10 hours.

[0065] As for the reaction method, for example, a known reaction method such as a batch reaction, a semi-continuous reaction or a continuous reaction can be selected.

[0066] The reaction can be carried out in a solvent or in the absence of a solvent. However, when the reaction is carried out in a solvent, it is preferred to remove the solvent during or after the reaction to ultimately eliminate the solvent. The method for removing the solvent is not limited to a specific method.

[0067] Based on the total amount of the moisture-curable hot-melt polyurethane resin adhesive, the amount of the phenylphosphonic acid zinc salt represented by formula (2) is 0.1% by mass or more, 10% by mass or less, or 0.1 to 10% by mass. Based on the total amount of the moisture-curable hot-melt polyurethane resin adhesive, the lower limit of the total content may be 0.3% by mass, 0.5% by mass, or 1% by mass. Based on the total amount of the moisture-curable hot-melt polyurethane resin adhesive, the upper limit of the total content may be 7%, 5%, or 3% by mass.

[0068] The moisture-curable hot melt polyurethane resin adhesive of the present embodiment may also contain other resins, such as previously known thermoplastic resins and thermosetting resins, and may also contain other additives. Examples of other additives include foam stabilizers, antioxidants, defoamers, UV absorbers, abrasive particles, fillers, pigments, dyes, colorants, thickeners, surfactants, flame retardants, plasticizers, lubricants, antistatic agents, heat-resistant stabilizers, adhesion-imparting agents, curing catalysts, stabilizers, fluorescent whitening agents, silane coupling agents, and waxes.

[0069] The present invention is further described in detail below based on examples. The present invention is not limited to the examples.

[0070] [Example 1]

[0071] (Production of Zinc Phenylphosphonate)

[0072] In a 1-liter four-necked flask, 10 parts by mass (63.3 mmol) of phenylphosphonic acid represented by formula (1) and 400 parts by mass of water were added to prepare an aqueous solution. To the flask, an aqueous solution prepared from 8.6 parts by mass (63.1 mmol) of zinc chloride and 200 parts by mass of water and 6.9 parts by mass of polyethylene glycol (Mn = 1,000) dissolved in 19.7 parts by mass of ethanol were further added and mixed together. Under stirring, 129 parts by mass of a 1.0 M sodium hydroxide aqueous solution was added to the solution within 3 hours to react. The precipitated white precipitate was filtered out, washed with water, and then dried under reduced pressure at 80°C for more than 2 hours to obtain a phenylphosphonic acid zinc salt represented by formula (2) as a white powder.

[0073] (Production of moisture-curable hot-melt polyurethane resin adhesives)

[0074] In a 1-liter four-necked flask, 30 parts by mass of polypropylene glycol (Mn = 1,000), 40 parts by mass of an aliphatic polyester polyol (Mn = 4,500) obtained by reacting 1,6-hexanediol (HD) and adipic acid (AA) with each other at a mass ratio of HD / AA = 46 / 54, and 30 parts by mass of an aromatic polyester polyol (Mn = 5,000) obtained by reacting 1,6-hexanediol (HD), neopentyl glycol (NPG), ethylene glycol (EG), isophthalic acid (iPA) and terephthalic acid (tPA) with each other at a mass ratio of HD / NPG / EG / iPA / tPA = 7 / 14 / 18 / 40 / 21 were mixed together and melted to prepare polyol (A).

[0075] Next, 1.2 parts by mass (1.0% by mass based on the total amount of the binder) of a powder of phenylphosphonic acid zinc salt represented by formula (2) obtained as described above was added to (A) as a crystal nucleating agent, and the mixture was heated to 110° C. and dehydrated under reduced pressure until the moisture content reached 0.05% by mass.

[0076] Subsequently, it was cooled to 70° C., 19 parts by mass of 4,4-diphenylmethane diisocyanate was added thereto, and then the mixture was reacted at 90° C. for 3 hours until the NCO content (%) became constant to obtain a moisture-curable hot-melt polyurethane resin adhesive.

[0077] [Comparative Example 1]

[0078] The same operation as in Example 1 was carried out except that the powder of the phenylphosphonic acid zinc salt represented by the formula (2) obtained as described above was not added to obtain a moisture-curable hot-melt polyurethane resin adhesive.

[0079] [Comparative Example 2]

[0080] The same operation as in Example 1 was carried out to obtain a moisture-curable hot-melt polyurethane resin adhesive, except that Ecopromote (produced by Nissan Chemical Corporation), which is a commercially available powder of phenylphosphonic acid zinc salt, was used instead of the powder of phenylphosphonic acid zinc salt represented by formula (2) obtained as described above.

[0081] [Comparative Example 3]

[0082] The same operation as in Example 1 was performed to obtain a moisture-curable hot-melt polyurethane resin adhesive, except that Ecopromote NP (produced by Nissan Chemical Corporation), which is a commercially available powder of phenylphosphonic acid zinc salt, was used instead of the powder of phenylphosphonic acid zinc salt represented by formula (2) obtained as described above.

[0083] [Evaluation of curing time (open time)]

[0084] Each of the obtained moisture-curable hot-melt polyurethane resin adhesives of the embodiment and the comparative example was made into a heated molten state at 120°C and coated on a polypropylene sheet as a substrate with a thickness of 50 μm. Next, the kraft paper as a surface member was placed on the adhesive layer coated as described above, and immediately placed in a constant temperature oven at 25°C. Based on the time point placed in the constant temperature oven, the time (in seconds) until the kraft paper no longer adheres to the adhesive layer was measured, and it was determined as the curing time at 35°C (open time at 35°C). In addition, based on the time point placed in the constant temperature oven, the time (in seconds) when the adhesive layer loses its adhesive feeling when touched with a finger was measured as the non-stick time at 35°C. The results are listed in Table 1.

[0085] [Evaluation of initial creep properties]

[0086] Each of the obtained moisture-curable hot-melt polyurethane resin adhesives was made into a heated molten state at 120°C, and the molten moisture-curable hot-melt polyurethane resin adhesive was coated on a polypropylene sheet having a width of 1 inch to a thickness of 50 μm, and then a medium-density fiberboard (MDF) was placed on the coated adhesive layer and bonded. After bonding for three minutes, a load of 150 g was applied to the MDF in a 90° direction in an atmosphere at 35°C, and the time (seconds) until the peeling length reached 4 cm was measured and determined as the initial creep property at 35°C. The results are listed in Table 1.

[0087] [Evaluation of initial peel strength]

[0088] Each of the obtained moisture-curable hot-melt polyurethane resin adhesives was made into a heated molten state at 120°C, and the molten moisture-curable hot-melt polyurethane resin adhesive was coated on a polypropylene sheet with a width of 1 inch to a thickness of 50 μm, and then a medium-density fiberboard (MDF) was placed on the coated adhesive layer and bonded. After bonding for three minutes, the MDF was peeled off in a room temperature atmosphere at 180°, and the tensile strength (N) during the process was measured and determined as the initial peel strength after 3 minutes. The results are listed in Table 1.

[0089] [Table 1]

[0090]

Claims

1. A method for producing a zinc salt of phenylphosphonic acid, the method comprising the step of reacting phenylphosphonic acid represented by formula (1) and a zinc compound with each other in water in the presence of polyethylene glycol: 。 2. The method for producing a phenylphosphonic acid zinc salt according to claim 1, wherein the amount of the zinc compound is 1 mol or less relative to 1 mol of the phenylphosphonic acid represented by the formula (1).

3. A powder of zinc phenylphosphonate represented by formula (2), which is obtained by the method for producing zinc phenylphosphonate according to claim 1 or 2: 。 4. Use of the powder according to claim 3 as a crystal nucleating agent.

5. A moisture-curable hot-melt polyurethane resin adhesive, comprising: an isocyanate-terminated polyurethane prepolymer; and The powder according to claim 3. 6 . The moisture-curable hot-melt urethane resin adhesive according to claim 5 , wherein the content of the powder is 0.1 to 10% by mass based on the entire amount of the moisture-curable hot-melt urethane resin adhesive.

Citation Information

Patent Citations

  • Method for producing phosphonic acid metal salt and thermoplastic resin composition containing phosphonic acid metal salt

    WO2011030822A1